Technological Advances in the Hemostasis Laboratory - Lippi, Giuseppe; Plebani, Mario; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2014)
Automation is conventionally defined as the use of machines, control systems, and information technologies to optimize productivity. Although automation is now commonplace in several areas of diagnostic testing, especially in clinical chemistry and immunochemistry, the concept of extending this process to hemostasis testing has only recently been advanced. The leading drawbacks are still represented by the almost unique biological matrix because citrated plasma can only be used for clotting assays and few other notable exceptions, and by the highly specific pretreatment of samples, which is particularly distinct to other test systems. Despite these important limitations, a certain degree of automation is also now embracing hemostasis testing. The more relevant developments include the growing integration of routine hemostasis analyzers with track line systems and workcells, the development of specific instrumentation tools to enhance reliability of testing (i.e., signal detection with different technologies to increase test panels, plasma indices for preanalytical check of interfering substances, failure patterns sensors for identifying insufficient volume, clots or bubbles, cap-piercing for enhancing operator safety, automatic reflex testing, automatic redilution of samples, and laser barcode readers), preanalytical features (e.g., positive identification, automatic systems for tube(s) labeling, transillumination devices), and postphlebotomy tools (pneumatic tube systems for reducing turnaround time, sample transport boxes for ensuring stability of specimens, monitoring systems for identifying unsuitable conditions of transport). Regardless of these important innovations, coagulation/hemostasis testing still requires specific technical and clinical expertise, not only in terms of measurement procedures but also for interpreting and then appropriately utilizing the derived information. Thus, additional and special caution has to be used when designing projects of automation that include coagulation/hemostasis testing because peculiar and particular requirements must be taken into account.
Keywords: coagulation; hemostasis testing; errors; automation; quality